Pengaruh Sikap, Norma Subjektif Dan Kontrol Perilaku Terhadap Minat Deposito Nasabah Prioritas Pada PT. Bank Tabungan Negara (Persero) TBK Kantor Cabang Padang - Tomi Angrico; Febsri Susanti (Jurnal Bintang Manajemen, 2024)
This research aims to examine and determine the influence of attitude, subjective norms, and behavioral control on the interest of priority customers' deposits at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office. This research is quantitative in nature. The primary data for this research were obtained through the distribution of questionnaires to priority customers at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office. The population of this study consisted of 272 individuals. The sampling technique used in this research was total sampling, resulting in a sample size of 272 respondents. The data analysis technique used was multiple linear regression and t-Statistical test. The research results indicate that attitude has a significant influence on the interest of customer deposits at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office, as reflected by the significance value (Sig.) of 0.035, which is lower than < 0.05 (α). Subjective norms have a significant influence on the interest of customer deposits at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office, as evidenced by a very low significance value, which is 0.000 < 0.05 (α). Behavioral control has a significant influence on the interest of customer deposits at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office, as reflected in the very low significance value of 0.000 < 0.05 (α). The variables Attitude (X1), Subjective Norms (X2), and Behavioral Control (X3) are able to explain or influence the variable of customer deposit interest at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office by 74.1%.